Spontaneous and experimental poisoning by nitrate/nitrite in cattle fed Avena sativa (oat) and/or Lolium spp. (ryegrass) Intoxicação espontânea e experimental por nitrato/nitrito em bovinos alimentados com Avena sativa (aveia) e/ou Lolium spp. (azevêm) - Jonck F.* (2013)
Epidemiological data, clinical and pathological findings of the spontaneous andexperimental poisoning by nitrate and nitrite in cattle fed oats (Avena sativa) and/or ryegrass (Lolium spp.), diphenylamine test, and the nitrate content in the samples of the pasture where the outbreaks occurred, are described. The disease occurs in different regions of the State of Santa Catarina, in which pastures have exuberant growth, after receiving excessive amounts of chemical and/or organic fertilizer, mainly when raining occurs after a period of dry wheather. The animals grazing these pastures quickly develop brown mucosa, tachypnea, staggering gait, frequent urination, bloating, lateral recumbency and death in few minutes or hours. At necropsy of four animals that died spontaneously, the main lesions found were brown mucosa, dark color of the blood (chocolate), intense red color of the skeletal muscles and of the left part of the myocardium. The experimental reproduction of the disease was performed in seven cattle, with pastures from four farms where the disease occurred. The animals were fed with fresh oats and ryegrass and/or hay of it. Four animals died, two became ill and recovered, and one was treated with 2mg/kg per body weight of methylene blue 1%, and one cattle did not show changes. Clinical signs and lesions of the diseased animals that died were similar to natural cases. Microscopic changes were not observed in spontaneous and experimental poisoning. The diphenylamine test was positive in all the farms where the outbreaks occurred. The chemical analysis performed on samples of the pastures from several farms, in which outbreaks of the disease occurred, ranged from 0.30to 3.36% of nitrate in the dry matter. The disease is associated with the ingestion of oats and/or ryegrass pastures heavily fertilized, which accumulates high levels of nitrate after a period of rain and is characterized by rapid breathing, dark-colored blood, brown mucous and rapid death.